2013
DOI: 10.1063/1.4788809
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind the high thermoelectric power factor of SrTiO3 by calculating the transport coefficients

Abstract: The thermoelectric power factor of SrTiO3 is unusually high with respect to its mobility and band gap. Good thermoelectrics usually have high mobility and a narrow band gap, but such properties are not found in SrTiO3. We have determined the mechanism behind the high power factor by calculating the transport coefficients. The key to understanding the power factor is that different effective masses contribute to different transport phenomena. The discrepancy between the effective mass for the conductivity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 48 publications
6
65
0
Order By: Relevance
“…However, by calculating the electronic structure of STO for different tilt angles (ESI †) we found that the coexistence of dispersive and dispersion-less bands at the bottom of the conduction band is retained for the range of tilt angles observed in the Nb-doped LNTO series, and the ratio of effective electronic mass for the two bands remains 5 for all tilt angles examined, which is similar to the values reported for cubic STO previously. 22 Tauc plots from diffuse reflectance data show that the parent and doped compositions of LNTO have band gaps of 3.2 eV, which is similar to STO (Fig. S8, Table S9, ESI †).…”
Section: J Namementioning
confidence: 74%
See 1 more Smart Citation
“…However, by calculating the electronic structure of STO for different tilt angles (ESI †) we found that the coexistence of dispersive and dispersion-less bands at the bottom of the conduction band is retained for the range of tilt angles observed in the Nb-doped LNTO series, and the ratio of effective electronic mass for the two bands remains 5 for all tilt angles examined, which is similar to the values reported for cubic STO previously. 22 Tauc plots from diffuse reflectance data show that the parent and doped compositions of LNTO have band gaps of 3.2 eV, which is similar to STO (Fig. S8, Table S9, ESI †).…”
Section: J Namementioning
confidence: 74%
“…20,21 Both p-and n-type semiconductors are needed for device fabrication, and it has been more difficult to achieve comparable performance in n-type oxides. By exploiting the band structure of the perovskite oxide SrTiO3 (STO), which has contributions from both light and heavy electrons at the Fermi level, 22 it is possible to achieve large power factors of 28-36 μWK -2 cm -1 at 300 K in n-type Sr1-xLaxTiO3-δ (x = 0.015-0.1) single crystals, however, the performance is negated by the large κ of ≈ 12 Wm -1 K -1 . 23 The nanostructuring approaches used to reduce κ in classical compound semiconductors and intermetallics by increasing grain boundary scattering are inefficient in titanate perovskites as the phonon MFP of SrTiO3 is 2-3 nm, requiring nanometer-sized grains for any noticeable effect on κ.…”
mentioning
confidence: 99%
“…Moreover, m * plays different roles in σ and S. For thermoelectric performance it is important to have both high S and high σ, which as discussed previously 59 have opposite dependences on both carrier concentration and effective mass. This conundrum can be resolved by certain complex band structures that exploit the different transport integrals that enter σ and S. [60][61][62][63][64][65][66] STO has a particular band shape arising from the degeneracy of the t 2g levels in an octahedral crystal field that gives effectively lower dimensional behaviour in transport even though the material is cubic, analogous to the case of PbTe. 65 The sharp onset of the DOS at the CBM reflects the low-dimensional nature of the electronic structure.…”
mentioning
confidence: 99%
“…13 Recently, Shirai et al casted another interpretation on the large thermopower in SrTiO 3 as following. 14 It is often said that the t 2g components of the d electrons form dispersionless and three-fold degenerate bands. However, the lift of the degeneracy as leaving from the Γ point should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%